2008
DOI: 10.1007/s00127-008-0470-6
|View full text |Cite
|
Sign up to set email alerts
|

Bed utilization in two differently organized community mental health services in Northern Norway: the VELO-project

Abstract: There may be bedrock of need for psychiatric beds regardless of system-organization. Distance may in general be a minor issue for utilization of psychiatric beds, and may primarily interact with patient- or contextual characteristics associated with acute situations. Activity of day-hospital services rather than outpatient consultations may affect utilization of sheltered homes. The main theoretical models are conceptually useful, although more research is needed to specify mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…In a previous study, we found that the rates of hospitalization were remarkably alike between the systems, with a population rate of 7.7 inpatients per 1000 (Vesterålen) vs. 8.4 per 1000 (Lofoten), and a bed-utilization rate of about 1 per 1000 inhabitants in both areas [27]. This suggests that the use of inpatient treatment is quite similar in the two service-systems.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…In a previous study, we found that the rates of hospitalization were remarkably alike between the systems, with a population rate of 7.7 inpatients per 1000 (Vesterålen) vs. 8.4 per 1000 (Lofoten), and a bed-utilization rate of about 1 per 1000 inhabitants in both areas [27]. This suggests that the use of inpatient treatment is quite similar in the two service-systems.…”
Section: Methodsmentioning
confidence: 81%
“…The DPCs, which provide the major part of all psychiatric services locally often differ in their organization of services. While some rely on several types of outpatient services locally in combination with inpatient services at larger centralized regional hospitals, other have beds available at small local psychiatric institutions [27,28]. The organizational differences may be of particular importance to the issue of involuntary admission, as in the study areas, only the Central Mental Hospital in Bodø admits inpatients involuntarily.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach may be especially applicable in countries where integrated inpatient and outpatient care is in place, such as parts of France [7] and Norway [26, 40]. …”
Section: Discussionmentioning
confidence: 99%
“…In Lofoten, this is reversed, with 90% of the inpatient stays at the hospital in Bodø, and only 10% are admitted locally (i.e. in the local somatic hospital) [26]. Consequently, the two systems may be termed a ‘decentralized care model’ (i.e.…”
Section: Methodsmentioning
confidence: 99%